Development and validation of bioanalytical method for the analysis of amlodipine in human plasma with optimized extraction method using design of experiment - Mohammed Helaluddin, Abul Bashar; Alaama, Mohamed; Awang, Mohamed; Abbas, Syed Atif (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2018)
SUMMARY. Amlodipine is antihypertensive drug belonging to calcium antagonist group. This study aims to apply experimental design for the optimization of extraction method of amlodipine from human plasma for higher and constant recovery. A chromatographic method involving HPLC (High Performance Liquid Chromatography) with DAD (Diode Array Detector) was developed and validated for the determination of amlodipine in human plasma with cetirizine as internal standard. Sample preparation for the extraction of amlodipine and cetirizine (internal standard) from plasma was optimized using DOE (Design of Experiment). Three different parameters namely solvent type, solvent volume and pH were monitored at different level for the optimization of sample preparation that would produce best recovery of the analytes. For this purpose, three level full factorial design, was conducted. The recovery of amlodipine and internal standard was determined using the developed and pre validated HPLC-DAD method with an Agilent 1100 HPLC system. Chromatographic separation of the analytes was obtained using phenomenix (150 × 4.5 mm, 5 μm) C18 column. The mobile phase consists of 35:65 v/v of ACN: 0.3% triethylamine with pH adjusted at 3 using phosphoric acid. Detection of analyte was conducted using a diode array detector at 237 nm wavelength. Design Expert 10.0 software was used to interpret all data obtained from the optimization study. For the parameters solvent and solvent volume, acetonitrile and 1 mL was found to be the optimum values required to extract amlodipine and internal standard while pH had no effect on the optimum recovery. The recovery of amlodipine and internal standard was 80-88 and 85-99%, respectively. RESUMEN. Amlodipina es un fármaco antihipertensivo que pertenece al grupo de antagonistas del calcio. Este estudio tiene como objetivo aplicar el diseño experimental para la optimización del método de extracción de amlodipina del plasma humano para una recuperación más alta y constante. Se desarrolló y validó un método cromatográfico que involucra HPLC (cromatografía líquida de alta resolución) con DAD (detector de arreglo de diodos) para la determinación de amlodipina en plasma humano con cetirizina como patrón interno. La preparación de la muestra para la extracción de amlodipina y cetirizina (patrón interno) del plasma se optimizó usando DOE (diseño de experimento). Se controlaron tres parámetros diferentes, a saber, el tipo de disolvente, el volumen del disolvente y el pH a diferentes niveles para la optimización de la preparación de la muestra que produciría la mejor recuperación de los analitos. Para este propósito, se realizó un diseño factorial completo de tres niveles. La recuperación de amlodipina y patrón interno se determinó usando el método HPLC-DAD desarrollado y prevalidado con un sistema Agilent 1100 HPLC. La separación cromatográfica de los analitos se obtuvo usando una columna fenix (150 × 4.5 mm, 5 μm) C18. La fase móvil consiste en 35:65 v/v de ACN: 0.3% de trietilamina con pH ajustado a 3 usando ácido fosfórico. La detección del analito se realizó usando un detector de red de diodos a una longitud de onda de 237 nm. Se utilizó el software Design Expert 10.0 para interpretar todos los datos obtenidos del estudio de optimización. Para los parámetros, se encontró que el solvente acetonitrilo y el volumen de solvente de 1 mL eran los valores óptimos requeridos para extraer amlodipina y el estándar interno, mientras que el pH no tuvo efecto sobre la recuperación óptima. La recuperación de amlodipina y el estándar interno fue 80-88 y 85-99%, respectivamente.